2014
DOI: 10.1186/s13048-014-0110-6
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptome of corona radiata cells from individual MІІ oocytes that after ICSI developed to embryos selected for transfer: PCOS women compared to healthy women

Abstract: BackgroundCorona radiata cells (CRCs) refer to the fraction of cumulus cells just adjacent to the oocyte. The CRCs are closely connected to the oocyte throughout maturation and their gene expression profiles might reflect oocyte quality. Polycystic ovary syndrome (PCOS) is a common cause of infertility. It is controversial whether PCOS associate with diminished oocyte quality. The purpose of this study was to compare individual human CRC samples between PCOS patients and controls.MethodsAll patients were stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Wo m e n w i t h P C O S s e e m t o u n d e rg o a l t e r e d folliculogenesis with arrested small follicles; they can also exhibit an altered follicular hormonal environment [181][182][183], which may interfere with oocyte maturation, metabolism, and competence acquisition. Altered expressions of various transcripts, such as those encoding insulin receptors [175], IGF-binding proteins and receptors [184], and genes related to meiotic cell cycle regulation [185] have been observed in CCs from women with PCOS, suggesting that these women experience disturbances or delays in CC maturation and differentiation [185] and/or compromises in CC function [175]. Other studies focusing on CCs from these women found changes in long noncoding RNAs (lncRNAs; e.g., XLOC_011402, ENST00000454271, ENST00000433673, ENST00000450294, and ENST00000432431) [7], miRNAs (17 were differentially expressed; hsa-miRNA-135b-5p was the most highly upregulated and hsa-miRNA-3940-5p was the only example of downregulation) [186,187], and the methylation patterns of specific gene [188] when compared to controls, indicating that these cells undergo epigenetic deregulation.…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%
“…Wo m e n w i t h P C O S s e e m t o u n d e rg o a l t e r e d folliculogenesis with arrested small follicles; they can also exhibit an altered follicular hormonal environment [181][182][183], which may interfere with oocyte maturation, metabolism, and competence acquisition. Altered expressions of various transcripts, such as those encoding insulin receptors [175], IGF-binding proteins and receptors [184], and genes related to meiotic cell cycle regulation [185] have been observed in CCs from women with PCOS, suggesting that these women experience disturbances or delays in CC maturation and differentiation [185] and/or compromises in CC function [175]. Other studies focusing on CCs from these women found changes in long noncoding RNAs (lncRNAs; e.g., XLOC_011402, ENST00000454271, ENST00000433673, ENST00000450294, and ENST00000432431) [7], miRNAs (17 were differentially expressed; hsa-miRNA-135b-5p was the most highly upregulated and hsa-miRNA-3940-5p was the only example of downregulation) [186,187], and the methylation patterns of specific gene [188] when compared to controls, indicating that these cells undergo epigenetic deregulation.…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%
“…Most of previous studies on PCOS focused on ovarian somatic cells, peripheral blood, or other cell types – for instance, CCs of PCOS patients display abnormal characteristics of gene expression, including dysregulated growth factors, steroid metabolism, cell cycle, steroid hormone biosynthesis, and hypomethylated genes related to the synthesis of lipid and steroid ( Haouzi et al, 2012 ; Wissing et al, 2014 ; Liu et al, 2016 ; Pan et al, 2018 ). Dysregulation of inflammatory function has also been found in PCOS patients through transcriptome and DNA methylation analysis of peripheral blood and granulosa-lutein cells ( Adams et al, 2016 ; Su et al, 2018 ; Hiam et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…These studies facilitated an understanding of the etiologic factors accounting for PCOS. Microarray or RNA sequencing analysis of oocytes and/or granulosa cells or cumulus cells (CCs) in women with PCOS has provided insights into the understanding of PCOS ( Wood et al, 2007 ; Haouzi et al, 2012 ; Wissing et al, 2014 ; Liu et al, 2016 ; Chen et al, 2019 ). In addition, studies focused on ovarian somatic cells or ovary and other tissues revealed the metabolic abnormalities in PCOS ( Ma et al, 2007 ; Corton et al, 2008 ; Huang et al, 2010 ; Zhao et al, 2017 ; Sanchez-Garrido and Tena-Sempere, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of previous studies on PCOS focused on ovarian somatic cells, peripheral blood or other cell types. For instance, cumulus cells of PCOS patients display abnormal characteristics of gene expression including dysregulated growth factors, steroid metabolism, cell cycle, steroid hormone biosynthesis and hypomethylated genes related to the synthesis of lipid and steroid 79,46 . Dysregulation of inflammatory function also has been found in PCOS patients through transcriptome and DNA methylation analysis of peripheral blood and granulosa-lutein cells 4749 .…”
Section: Discussionmentioning
confidence: 99%